Analisis perbandingan kinerja keuangan perusahaan prospector dan defender (studi pada perusahaan manufaktur yang terdaftar di bursa efek indonesia periode tahun 2010-2012) - Erina Sudaryati; Farida Amelia ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2015)
In an increasingly competitive conditions, companies are required to develop strategies to create competitive advantage. Miles and Snow devide firm’s strategy into four types, which are prospector, defender, analyzer and reaction, with prospector and defender as the two extremes strategies.The determination of the company’s strategy both prospector and defender will have an impact on corporate performance, especially the company’s financial performance. The objectives of this research are to empirically examine the differences in financial performance between prospector and defender firms. Financial performance are measured by sales growth, income growth, dividend payout ratio, and return on investment. The definite selection between prospector and defender firms using 3 (three) control variables are employee growth to total net sales ratio (EMPSAL), price to book value ratio (PBV), and capital expenditure to total asset (CAPTA). Population of this research are the manufacturing firms listed in Indonesian Stock Exchange in 2010 to 2012 which number of population that used were 136 firms. The samples are collected using purposive sampling method. Selection of sample types prospector and defender analyzed using cluster analysis of the three variables that exist. Financial performance data in this study were analyzed using Mann-Whitney test with the help of software SPPS 17.0. The result of this research show that 38 firms become the samples, 21 firms are categorized as prospectors and 17 firm are categorized as defenders. Average sales and income growth of prospector firms are higher than defender firms, the result is significant. Dividend payout ratio and Return On Investment of prospector firms are smaller than defender firms, the result is significant.Keywords: Prospector and Defender, Sales Growth, Income Growth, Dividend Payout,                    Return On Investment